Pengaruh Pemeriksaan Pajak, Penagihan Pajak, dan Jumlah Pengusaha Kena Pajak Terhadap Penerimaan Pajak Pertambahan Nilai (PPN) - Habibah, Sinta; Syalitri, Lili; Meiriasari, Vhika (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the effect of Tax Audits, Tax Collection, and the Number of VAT-Registered Taxpayers (PKP) on Value Added Tax (VAT) Revenue at the KPP Pratama Sekayu. The research method used is quantitative with a descriptive and inferential analysis approach. The data used in this study was obtained from KPP Pratama Sekayu by collecting primary data through questionnaires and secondary data from related reports. Data analysis was conducted using SPSS version 26. The results show that Tax Audits do not significantly affect VAT revenue, possibly due to the low follow-up on audit results and other administrative factors. In contrast, Tax Collection and the Number of PKP significantly affect VAT revenue, with effective tax collection increasing VAT revenue. The simultaneous test (F-test) shows that, overall, the variables of Tax Audits, Tax Collection, and the Number of PKP significantly affect VAT Revenue, with an R value of 0.458, meaning that approximately 45.8% of the variation in VAT revenue can be explained by these three variables. This study recommends that KPP Pratama Sekayu improve the effectiveness of tax audits and collections and strengthen taxpayer compliance through more intensive education and outreach.